The conceptualization of depression among Filipino seafarers - Fernandez, Karina Therese G (Archīum Ateneo, 2018)
The Center for Epidemiological Studies – Depression (CES-D) scale is a well-validated and frequently used measure for assessing symptoms associated with depression. This scale was developed primarily on the basis of American populations, however, and previous research has suggested that the original factor structure may not be appropriate for all populations. One such population is the Filipino population. This study represents the first study we are aware of to examine the factor structure of the CES-D scale in a sample of Filipino seafarers. Seafaring is considered a high stress and high risk occupation. Based on data collected from 135 Filipino seafarers, we conducted factor analyses to identify the appropriate factor structure for the CES-D in this population. We found that a three-factor structure better described the responses of Filipinos in our sample than the standard four-factor structure. The Filipino factor structure appears to collapse depressive affect and somatic factors found in previous research, while including a specific factor of social-focused symptoms of depression. This structure maintains the positive affect factor found in previous work. Implications of this for clinical psychology assessment and practice in the Philippines are discussed.